2019
DOI: 10.1038/s41598-018-37028-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuron/Glial Antigen 2-Type VI Collagen Interactions During Murine Temporomandibular Joint Osteoarthritis

Abstract: The degeneration of articular cartilage underscores the clinical pathology of temporomandibular joint osteoarthritis (TMJ-OA) and is promoted through dysfunctional biochemical or biophysical signaling. Transduction of these signals has a multifaceted regulation that includes important cell-matrix derived interactions. The matrix encapsulating the cells of the mandibular condylar cartilage (MCC) is rich in type VI collagen. Neuron/glia antigen 2 (NG2) is a type I transmembrane proteoglycan that binds with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Whole mount immunolabeling of type VI collagen imaged using two-photon fluorescence (TPF) does reconstruct this pericellular matrix in the superficial layer ECM ( Fig 2B ). The general organization of pericellular type VI collagen from TPF matches that observed from confocal immunofluorescence [ 26 , 30 ], with the strongest stain encapsulating the cells and weak staining in the interterritorial matrix between cells. SHG and superficial layer TPF colocalization is weak in non-surgical control MCC ( Fig 2C ).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Whole mount immunolabeling of type VI collagen imaged using two-photon fluorescence (TPF) does reconstruct this pericellular matrix in the superficial layer ECM ( Fig 2B ). The general organization of pericellular type VI collagen from TPF matches that observed from confocal immunofluorescence [ 26 , 30 ], with the strongest stain encapsulating the cells and weak staining in the interterritorial matrix between cells. SHG and superficial layer TPF colocalization is weak in non-surgical control MCC ( Fig 2C ).…”
Section: Resultssupporting
confidence: 53%
“…Experimental endpoints included four time points: 4, 8, 12, and 16 weeks post-injury. Time points were chosen based on previous descriptions of the mouse model [ 10 , 26 ]. All experiments using vertebrate animals were approved by the University of Illinois at Chicago Animal Care Committee and performed in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporomandibular joint osteoarthritis was induced by unilateral partial discectomy 24,26) . Seven-week-old, male c57 BL/6J mice were anesthetized with ketamine (100 mg/kg) and xylazine (5 mg/kg).…”
Section: Unilateral Partial Discectomy Modelmentioning
confidence: 99%
“…A study by Alexopoulos and colleagues ( 6 ) showed that Col6α1 ‐KO mice had accelerated joint degeneration in the femoral head leading to early development of OA as well as delayed ossification. Yotsuya and colleagues ( 45 ) showed changes in the distribution of type VI collagen and Neuron/Glial Antigen 2 (NG2), a cell membrane proteoglycan that binds to type VI collagen, in the TMJ during surgically induced osteoarthritis. The authors suggest that type VI collagen could be mediating cartilage degeneration through interactions with NG2.…”
Section: Discussionmentioning
confidence: 99%